India towards Measles Eradication - Gohiya, Poorva; Gedam, D Sharad (International Journal of Medical Research and Review, 2014)
After successful eradication of Polio; India is now moving forward for Measles control and elimination. The vision of “a world without measles” is supported by WHO, UNICEF and other partners in newly released Global Measles and Rubella Strategic Plan 2012-2020.